Neurotrophic Keratopathy in Systemic Diseases: A Case Series on Patients Treated With rh-NGF - Meduri, Alessandro; Oliverio, Giovanni William; Valastro, Antonio; Azzaro, Claudia; Camellin, Umberto; Franchina, Francesco; Inferrera, Leandro; Roszkowska, Anna; Aragona, Pasquale (Frontiers in Medicine, 2022)
Purpose: To evaluate the prevalence, clinical ocular presentation and corneal healing in moderate and severe neurotrophic keratopathy (NK) caused by systemic diseases and treated with rh-NGF. Setting: Department of Biomedical and Dental Sciences and Morphofunctional Imaging, Ophthalmology Clinic, University of Messina, Italy. Design: Retrospective observational study of case series. Materials and Methods: In this retrospective observational study eleven patients (5 female and 6 males) aged from 24 to 88 years (55.4 ± 21.3 years) with moderate and severe NK caused by systemic diseases were enrolled. The VAS questionnaire was dispensed. The ocular examination comprised slit lamp evaluation, ocular surface assessment with Keratograph 5M (Oculus, Germany), corneal sensitivity with Cochet-Bonnet esthesiometer (Lunneaux, France) and corneal thickness measurement with AC-OCT (DRI, Triton, Topcon, Japan). The underlying systemic causes of NK were determined. Results: The main cause of NK was post-neuroma surgery (36%), followed by diabetes (18%). The remaining causes were rheumatoid arthritis (9%), post-traumatic (9%), post-surgery (9%), atopia (9%), Graves’ disease (9%). Seven eyes presented severe grade of NK with corneal ulcer and in 4 a moderate grade was registered. The rh-NGF(Cenegermin) was administered with a standard protocol 1 drop 6 times daily for 8 weeks. The complete healing of all corneal defects was registered at the end of the treatment. Conclusions: The post-neuroma surgery was the most common cause of NK and severe grade was clinically more represented. The rh-NGF proved effective to promote corneal recovery with all defects healed after the treatment.